Metformin during Pregnancy: Effects on Offspring Development and Metabolic Function - Jorquera, Gonzalo; Echiburú, Bárbara; Crisosto, Nicolás; Sotomayor-Zárate, Ramón; Maliqueo, Manuel; Cruz, Gonzalo (Frontiers in Pharmacology, 2020)
Maternal obesity during pregnancy and gestational diabetes mellitus (GDM) are both associated with of several postnatal diseases in the offspring, including obesity, early onset hypertension, diabetes mellitus, and reproductive alterations. Metformin is an oral drug that is being evaluated to treat GDM, obesity-associated insulin resistance, and polycystic ovary syndrome (PCOS) during pregnancy. The beneficial effects of metformin on glycemia and pregnancy outcomes place it as a good alternative for its use during pregnancy. In this line of thought, improving the metabolic status of the pregnant mother by using metformin should avoid the consequences of insulin resistance on the offspring's fetal and postnatal development. However, some human and animal studies have shown that metformin during pregnancy could amplify these alterations and be associated with excessive postnatal weight gain and obesity. In this minireview, we discuss not only the clinical and experimental evidence that supports the benefits of using metformin during pregnancy but also the evidence showing a possible negative impact of this drug on the offspring's development.